Transformation of Resource-Based Cities: The Case of Benxi - Wang, Xintong; Liu, Hanbin; Chen, Zhujun (Frontiers in Environmental Science, 2022)
Resource-based cities, which emerge due to the large-scale industrialization of China, mainly rely on local natural resources for industrial layout and economic development. However, resources have been gradually exhausted due to overuse, resulting in a series of negative impacts on the environment and resources. In order to realize long-term sustainable development and avoid falling into the “resource curse,” measures such as industrial structure adjustment and technological upgrading to promote the transformation of these cities ought to be implemented. Taking Benxi, one of the most typical mineral resource-based cities in China, as an example, this study discusses the economic and environmental performance and existing problems in the local transformation process, comparing it with successful transformation patterns of global mineral resource-based cities. On this basis, a series of policy suggestions together with possible ways toward sustainable development are put forward and summarized.